ANALYSIS OF FACTORS AFFECTING INDONESIA'S CRUDE PALM OIL (CPO) EXPORTS IN THE GLOBAL MARKET 1992 - 2022 - Awaliyah, Nissa Nur; Iranto, Dicky; Mukhtar, Saparuddin (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
One of the factors that can increase a country's Gross Domestic Product (GDP) is through international trade activities. This study aims to identify the factors that influence Indonesia's Crude Palm Oil (CPO) exports in the global market, focusing on certain variables. The research method used is a quantitative approach using secondary data from sources such as Bank Indonesia, World Bank, UN Comtrade, Statistics Indonesia, and GAPKI. Time series data from 1992 to 2022 was used in this analysis. The analysis was conducted using multiple linear regression models with the E-views 12 analysis tool. The results showed that the exchange rate and international CPO price had a positive and significant influence on Indonesia's CPO export volume. However, the inflation variable was found to have a negative, albeit insignificant, influence on Indonesia's CPO export volume.